The Effect of Lack of Control on Unsafe Action on Workers in the X Apartment Construction Project - Salmah, Umi; Syahri, Isyatun Mardhiyah; Syahputra, Dimas Aditya (PT FORMOSA CENDEKIA GLOBAL, 2024)
Work accidents are generally caused by two main factors: unsafe actions and unsafe conditions. According to the domino theory, lack of control and basic causes are the main causes of hazardous actions. This study aims to analyze the determinants of the causes of unsafe actions in the construction project of X Apartment. This research is a quantitative study with a crossectional design, conducted at the X Apartment construction project from September 2023 to March 2024. The population was 200 workers, with a sample of 134 workers based on the Slovin formula. Data analysis used linear regression tests and path analysis. The results showed that the highest age was 22-37 years as many as 95 people (70.9%) and the highest level of education among workers was high school as many as 85 people (62.9%). There is an effect of lack of control on unsafe action (0.001), It is recommended that workers pay attention to their physical capabilities and not push themselves beyond the limits of their physical abilities. Management is also expected to pay attention to the physical capabilities of workers to avoid unsafe acts